Environmental Drivers of Questing Activity of Juvenile Black-Legged Ticks (Acari: Ixodidae): Temperature, Desiccation Risk, and Diel Cycles. Issue 1 (2nd August 2019) - Thomas, Christina E; Burton, Emily S; Brunner, Jesse L
Abstract: Vector feeding behavior can have a profound influence on the transmission of vector-borne diseases. In the case of black-legged ticks, Ixodes scapularis Say, which vectors the agents of Lyme disease, babesiosis, and other pathogens, the timing and propensity of questing can determine which hosts are fed upon as well as the risk of contact with humans. Yet we know little about the controls and constraints on tick host-finding behavior under natural conditions. Ticks must balance the need to quest for blood meal hosts with the risk of desiccation, all on a fixed energy budget. Prior research, primarily in the laboratory, has shown that questing activity varies with conditions (e.g., temperature, relative humidity), light-dark cycles, and energy reserves, but the findings have been idiosyncratic and the dominant factor(s) in nature remains unknown. We measured questing activity of nymphs and larvae throughout the day and night and over several weeks in enclosures across a range of suitable tick habitats within a site in the Northeast. Activity of nymphs increased slightly during dawn and dusk, opposite of larvae, and declined slightly with air temperature and rain, but these patterns were weak and inconsistent among replicate sites. Rather it appears a fraction of ticks were questing most of the time, regardless of conditions. Our study suggests neither climatic conditions or light-dark cycles have appreciable influence on tick questing behavior.